Higher Baseline Serum Irisin Decreases Risk for Body Mass Index Increment in Chinese Populations: A 3.2-Year Cohort Study - Liu, Ruoyi (Diabetes Ther, 2019)
INTRODUCTION: Irisin, a newly discovered myokine, exerts beneficial effects on energy metabolism. However, published results from studies examining the relationship between irisin concentration and obesity have been conflicting. The aim of our study was to investigate the association between serum irisin level and obese individuals with different body mass index (BMI) values and to explore the question of whether serum irisin can predict the risk of increases in the BMI. METHODS: This study based on the data collected in the Risk Evaluation of cAncers in Chinese diabeTic Individuals: a lONgitudinal (REACTION). The cross-sectional cohort study was carried out from May 2011 to August 2011, and a longitudinal cohort study was conducted from July 2014 to October 2014 to complete the first 3.2-year follow-up. We enrolled 93 low-weight subjects (BMI < 18.5 kg/m(2)), 94 normal-weight subjects (BMI 18.5–23.9 kg/m(2)), 98 overweight subjects (BMI 24.0–27.9 kg/m(2)) and 93 obese subjects (BMI ≥ 28 kg/m(2)). Subjects in the normal-weight, overweight and obese groups were selected to match low-weight subjects by age and sex. Serum samples were obtained from all subjects to determine the irisin level. RESULTS: Subjects with a higher serum irisin level tended to have significantly lower changes in BMI and body fat percentage and higher baseline high-density lipoprotein cholesterol level (p < 0.05). No significant correlation was observed between serum irisin level and the baseline obesity index. Serum irisin level was positively correlated to an active lifestyle (i.e. physical activity; β = 1.138, p  = 0.032) and negatively correlated to fasting plasma glucose level (β = − 0.996, p  = 0.023), changes in BMI (β = − 0.533, p  = 0.002), waist circumference (β = − 0.102, p  = 0.018), body fat percentage (β = − 0.457, p  = 0.001) and Chinese visceral adiposity index (β = − 0.280, p  = 0.028). After adjustment for cofactors, higher baseline serum irisin was an independent factor for a decreased BMI increment (baseline serum irisin: odds ratio 0.747, 95% confidence interval 0.652–0.949, p  = 0.002). CONCLUSIONS: Higher serum irisin at baseline independently predicted a lower BMI increment in Chinese populations.